Propolis-Based Nanostructured Lipid Carriers for α-Mangostin Delivery: Formulation, Characterization, and In Vitro Antioxidant Activity Evaluation - Cecep Suhandi; Gofarana Wilar; Ronny Lesmana; Felix Zulhendri; Ine Suharyani; Nurhasni Hasan; Nasrul Wathoni (Molecules, 2023)
α-Mangostin (a xanthone derivative found in the pericarp of Garcinia mangostana L.) and propolis extract (which is rich in flavonoids and phenols) are known for their antioxidant properties, making them potential supplements for the treatment of oxidative stress-related conditions. However, these two potential substances have the same primary drawback, which is low solubility in water. The low water solubility of α-mangostin and propolis can be overcome by utilizing nanotechnology approaches. In this study, a propolis-based nanostructured lipid carrier (NLC) system was formulated to enhance the delivery of α-mangostin. The aim of this study was to characterize the formulation and investigate its influence on the antioxidant activity of α-mangostin. The results showed that both unloaded propolis-based NLC (NLC-P) and α-mangostin-loaded propolis-based NLC (NLC-P-α-M) had nanoscale particle sizes (72.7 ± 1.082 nm and 80.3 ± 1.015 nm, respectively), neutral surface zeta potential (ranging between +10 mV and −10 mV), and good particle size distribution (indicated by a polydispersity index of <0.3). The NLC-P-α-M exhibited good entrapment efficiency of 87.972 ± 0.246%. Dissolution testing indicated a ~13-fold increase in the solubility of α-mangostin compared to α-mangostin powder alone. The incorporation into the propolis-based NLC system correlated well with the enhanced antioxidant activity of α-mangostin (p < 0.01) compared to NLC-P and α-mangostin alone. Therefore, the modification of the delivery system by incorporating α-mangostin into the propolis-based NLC overcomes the physicochemical challenges of α-mangostin while enhancing its antioxidant effectiveness.